Supportive treatments and whey proteins in cancer patients - Trivisonne, R. (Progress in Nutrition, 2011)
SummaryIn the treatment of neoplastic patients many toxicities caused by chemo or radiotherapy are related to the formation of free radicals and to the oxidative stress and have been treated with antioxidants products. Besides some vitamins (A, E, C, carotenoids, etc) few specific antioxidants are used in the supportive treatment in medical oncology: amifostine, dexrazoxane, sodium 2-sulfanylethanesulfonate (MESNA), glutathione (GSH). The aminoacids included in the milk whey proteins (cysteine and glutamic acid) as precursors of GSH can increase the tissue concentration of GSH, stimulate the immunologic system, detoxify potential carcinogens and neutralize the Reactive Oxygen Species (ROS). The milk proteins are used in the supportive treatment of the neoplastic patient especially for the antioxidants properties of GSH. A whey protein concentrate supplemented with a high content of cysteine and glutamic acid, as precursors of GSH, given to breast cancer patients under chemo or radiotherapy, has led to an increase of BAP test (plasma anti-oxidant capacity) and of d-ROMs test (plasma oxidant capacity). Cysteine as precursor of milk proteins as well as of GSH may also be considered an important agent in the supportive treatment of neoplastic cachexia. We still need controlled clinical trials and reliable guide lines in order to use natural or pharmaceutical supplements in medical oncology.Interventi di supporto e proteine del siero di latte nel paziente oncologicoRiassuntoMolte delle tossicità da chemioterapia e da radioterapia correlate alla formazione di radicali liberi e allo stress ossidativo sono state trattate con l’impiego di anti-ossidanti. Oltre alle vitamine (A, E, C, carotenoidi, etc) ci sono alcuni particolari anti-ossidanti, che vengono impiegati nel trattamento di supporto in chemioterapia oncologica: amifostina, dexrazoxane, sodio 2-sulfaniletanosulfonato (MESNA), glutatione (GSH). Gli aminoacidi contenuti nelle proteine del siero di latte (cisteina e acido glutammico) in quanto precursori del GSH sono in grado di aumentare in maniera rilevante la concentrazione tissutale di GSH, di stimolare il sistema immunitario, di detossificare i potenziali cancerogeni e di distruggere le specie reattive centrate sull’ossigeno (Reactive Oxygen Species, ROS). Le proteine del siero di latte sono impiegate nel trattamento di supporto del paziente oncologico specie in riferimento alle capacità antiossidanti del GSH. Un concentrato di proteine di siero di latte addizionato di cisteina e acido glutammico (come principali precursori del GSH) in aggiunta al trattamento oncologico standard (radioterapia e chemioterapia) in pazienti con neoplasia della mammella ha fatto riscontrare un incremento della capacità anti-ossidante del plasma (misurata con il BAP test) e della capacità ossidante del plasma (misurata con il d-ROMs test). La cisteina come precursore sia delle proteine sieriche che del GSH (antiossidante cellulare) può essere considerata un importante supporto nella cachessia neoplastica. Mancano tuttora studi clinici controllati e linee guida accreditate per l’impiego degli integratori naturali o farmacologici in ambito oncologico.